Context-responsive pedagogy in English language teaching in Indonesian Islamic boarding schools - Madkur, Ahmad; As'ad, Muhammad Syihab; Prayogo, Agus; Sunarwan, Aisyah; Siregar, Syahreni; Harya, Trisna Dinillah; Irwansyah, Dedi (Journal of Education and Learning (EduLearn), 2024)
English language teaching (ELT) in Islamic boarding schools in Indonesia, commonly known as pesantren, presents a unique context that requires a tailored pedagogical approach. This study aimed to explore the application of context-responsive pedagogy in ELT within the unique context of Islamic boarding schools in Indonesia. This qualitative study employed semi-structured interviews and classroom observation as data generation methods to gain insights into the experiences and perspectives of English language teachers regarding the implementation of context-responsive pedagogy in English language instruction. The findings revealed the importance of understanding learner needs, incorporating authentic materials, promoting cultural sensitivity, and effective use of technology in ELT practices in Islamic boarding school contexts. This study delves into how English language teachers navigated and negotiated their practices with the socio-cultural and religious values entrenched in this institution. It also highlighted the challenges English language teachers in this school context faced in the implementation of context-responsive pedagogy. Eventually, this research provides valuable insights for ELT practitioners, policymakers, and researchers interested in incorporating context-specific pedagogy to optimize ELT in Islamic boarding schools and similar educational contexts.